2010
DOI: 10.1111/j.1582-4934.2010.01043.x
|View full text |Cite
|
Sign up to set email alerts
|

Functions of ICC‐like cells in the urinary tract and male genital organs

Abstract: Interstitial cells of Cajal (ICC)-like cells (ICC-LCs) have been identified in many regions of the urinary tract and male genital organs by immunohistochemical studies and electron microscopy. ICC-LCs are characterized by their spontaneous electrical and Ca2+ signalling and the cellular mechanisms of their generation have been extensively investigated. Spontaneous activity in ICC-LCs rises from the release of internally stored Ca2+ and the opening of Ca2+-activated Cl− channels to generate spontaneous transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 82 publications
2
23
0
Order By: Relevance
“…ICC-LCs are considered to act as urinary electrical pacemaker cells, instigating smooth muscle contraction (12). ICC-LCs are defined by their characteristic spindle shape and immunoreactivity to Kit in the mature upper urinary tract of mice and humans (28,29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ICC-LCs are considered to act as urinary electrical pacemaker cells, instigating smooth muscle contraction (12). ICC-LCs are defined by their characteristic spindle shape and immunoreactivity to Kit in the mature upper urinary tract of mice and humans (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…Interstitial cells of Cajal-like cells (ICC-LCs), marked by Kit expression, are localized throughout the upper urinary tract and have morphologic and molecular characteristics similar to those of intestinal pacemaker cells (11)(12)(13). Inhibition of Kit activity in ureter explants using neutralizing antibodies results in perturbation of unidirectional peristalsis, but not smooth muscle cell differentiation, which suggests that Kit function is required for ureter peristalsis (11).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have shown that IC exist within DSM bundles of various mammalian species [79]. Previous work with rabbit DSM suggests that cyclooxygenase-mediated signaling between IC and adjacent DSM bundles may play a role in the generation of LARC via prostaglandin signaling with these findings supporting the fact that increased prostaglandin levels are seen in patients with OAB-type symptoms [24].…”
Section: Discussionmentioning
confidence: 88%
“…IC in the lower urinary tract of mammals demonstrate spontaneous periodic calcium transients that may generate or modulate LARC [9,10]. Additionally, DSM cells are able to myogenically generate spontaneous activity and the frequency of this activity is increased in DSM samples taken from patients with overactive bladder syndrome (OAB) [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the telocytes have been observed recently in skeletal muscle [48,49], trachea [50] and lungs [50,51], cardiac tissues [47,52], urogenital tract [53], and exocrine pancreas [54]. To date, there is only one study on the parotid telocytes [11].…”
Section: Discussionmentioning
confidence: 97%